Genomic : metabolomics exploration of "Streptomyces" sp. b81 in the search for new bioactive compounds with antibacterial and antiproliferative activities = Exploração genômica: metabolômica de streptomyces sp. b81 na busca de novos compostos bioativos com atividades antibacteriana e antiproliferativa - Clavo, Rene Flores, 1986- (2022)
Orientador: Fabiana Fantinatti Garboggini